Potential of Red Betel Leaf Extract (Piper crocatum) and Siwak (Salvadora persica) Against Staphylococcus Aureus Bacteria - Member Reni Purba; Steven Wijaya; Ananda Kasuma (HM Publisher, 2022)
Background. One of the bacteria that cause oral cavity infection is Staphylococcus aureus. This study aims to explore the antibacterial potential of red betel extract and siwak extract against Staphylococcus aureus bacteria, in vitro. Methods. This research is an in vitro experimental study to assess the diameter of the inhibition zone of red betel leaf extract and siwak against Staphylococcus aureus. The extract was made from red betel leaf simplicia and siwak wood with a dose of 50% each. The bacterial suspension was made by taking one pure colony from a test tube. Data analysis was performed using SPSS version 25 software. Results. Red betel leaf extract 50% showed the largest diameter of the inhibition zone, namely 9.1 ± 0.68 mm. Meanwhile, the siwak extract showed a smaller inhibition zone diameter of 7.9 ± 0.68 mm. One-way ANOVA analysis showed that there was a significant difference between the diameters of the inhibition zones of each test group. Conclusion. Red betel leaf extracts are 50% greater in inhibiting the growth of Staphylococcus aureus than 50% siwak extract.